Determination of the Best Coating Parameters for Adhesion Strength and Hardness Using Taguchi Method - Ishiaka S. ARUDI; Samson BALOGUN, (UNIABUJA Journal of Engineering and Technology (UJET), 2025)
Because of its unique properties, such as high strength, resistance to corrosion, and biocompatibility, titanium-based alloys are among the metals used in biomedical implants the most frequently. The objective of this work was to cover the surfaces of TiN-coated Ti-51at. %Ni and Ti-27at. %Nb alloys to improve their adhesion strength and surface hardness. Titanium Nitride (TiN) coatings on substrates were produced using the physical vapour deposition magnetron sputtering technique. The deposition parameters, which included temperature, power, nitrogen flow rate and bias voltage, were varied during the process. To keep the experimental runs to nine, the Taguchi orthogonal array standard 9-run matrix L9(34) and Taguchi technique of optimising parameters through experiment design were employed. 370 W, 4.7 sccm, 50 V, and 100 oC were the combination of parameters that produced the best Ti/TiN coating adhesion on Ti-51 at %Ni and the nitrogen flow rate at 4.7sccm added more to the coating's adhesive strength, according to the studies. Ti/TiN coating on Ti-27 at %Nb was investigated using a range of process parameters, such as nitrogen flow rate, temperature, bias voltage, and DC power. Maximum surface hardness and adhesion strength may be achieved at the following ideal values: 370 W, 4.7 sccm, 15 oC, and 100 V, and 6.7 sccm, 150 oC, 100 V, and 300 W, respectively. Using the process parameters of nitrogen flow rate, temperature, bias voltage, and DC power, Ti/TiN was successfully deposited on Ti-25 at %Ta. According to the Taguchi optimisation technique, the best parameter combinations for coating strength and surface hardness are 4 sccm, 150 oC, 75 V, and 370 W, respectively.